2017
DOI: 10.1016/j.aller.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic values for egg white specific IgE levels with the skin prick test in Turkish children with egg white allergy

Abstract: Along with the determination of the diagnostic values of communities, the rapid and accurate diagnosis of the children with a food allergy will be ensured, and the patient follow-up will be made easier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A previous study showed that for all age groups, the value of 5 mm for an SPT was found to be significant with a 96.4% positive predictive value (PPV) and 97.8% specificity. 26 Another study performed in 5,276 infants showed SPT thresholds with 95% PPVs for food allergy were 8 mm or greater for peanut (95% CI, 7-9 mm), 4 mm or greater for egg (95% CI, 3-5 mm), and 8 mm or greater for sesame (95% CI, 5-9 mm). 27 A further study showed the predictive decision point for an egg white wheal was 9.5 mm, for a milk wheal was 9.5 mm, and for a wheat wheal was 6.5 mm, but their highest accuracy rates were low at 25.8%, 26.8%, and 34.4%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study showed that for all age groups, the value of 5 mm for an SPT was found to be significant with a 96.4% positive predictive value (PPV) and 97.8% specificity. 26 Another study performed in 5,276 infants showed SPT thresholds with 95% PPVs for food allergy were 8 mm or greater for peanut (95% CI, 7-9 mm), 4 mm or greater for egg (95% CI, 3-5 mm), and 8 mm or greater for sesame (95% CI, 5-9 mm). 27 A further study showed the predictive decision point for an egg white wheal was 9.5 mm, for a milk wheal was 9.5 mm, and for a wheat wheal was 6.5 mm, but their highest accuracy rates were low at 25.8%, 26.8%, and 34.4%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Although the criteria for SPT results used for the interpretation of sensitization vary in the literature [1, 13,14], a mean wheal diameter greater than 3 mm in relation to that of the negative control is commonly interpreted as the occurrence of sensitization [15].…”
Section: Discussionmentioning
confidence: 99%
“…These factors are believed to have increased the quality of the diagnosis in the current study. Furthermore, our method has a higher accuracy than the methods used in previous studies that examined the specificity of SPT with HEw in patients of similar age groups [13,14]. Although the cutoff value of SPT results was used as a criterion for performing the OFC, this criterion may not be suitable for pediatric patients and should be modified depending on the age and the guardians' preferences, which is reflective of real-world clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have shown that serum egg sIgE values correlate with oral food provocation test results and 95% positive predictive values for egg sIgE levels have been determined. It has been shown that an egg white sIgE level ≥ 7 kU/L has a 95% positive predictive value for positive provocation in children older than 2 years, and ≥ 2kU/L has a 95% positive predictive value in children 2 years or younger (12). Since the egg-specific IgE value (7 kU/L) of our patient at the age of 13 months was above the predictive value, no food provocation test was performed.…”
Section: Discussionmentioning
confidence: 81%